Boards Characteristics and Earnings Quality: UK Evidence - Nur, Nalini (2016)
This study attempts to observe the effect of board characteristics of non-financial UK firms on their earnings qualities. Using 259 firms out of the total 351 constituents of FTSE 350 during 2012 until 2015, we employ the modified-Jones model to calculate the abnormal accruals as proxies for earnings quality. We pay attention to five aspects of board characteristics: the board size, the percentage of independent directors; the number of board meetings in a year, Chief Executive Officer (CEO) age, and Chief Financial Officer (CFO) age. We find that the earnings quality will increase when firms have higher percentages of independent directors. Further, young CEOs lead to better earnings qualities compare to old CEOs, particularly old CEOs in their final pre-retirement year. Finally, we do not find the impact of board size, the number of board meetings and CFO age on earnings quality.